IMPLEMENTASI PERATURAN DAERAH KABUPATEN CIANJUR NOMOR 01 TAHUN 2012 DALAM PERLINDUNGAN TENAGA KERJA INDONESIA KE LUAR NEGERI TAHUN 2012-2016 - Ningrum, Elis Salsiah; Rahmawati, Rita; Salbiah, Euis (Administratie: Jurnal Administrasi Publik, 2019)
This study aims to analyze the implementation of one of the regional regulations concerning the Placement and Protection of Indonesian Workers Abroad. This study used a convergent parallel mixed approach. The research used a policy research method with a descriptive explanation level. The data analysis techniques used are data reduction, data presentation, verification, and weight mean score. This study produces data findings that the Local Government has implemented the Regional Regulation on Protection of Indonesian Workers overseas well. It evidenced by the acquisition of an average score of 2.98 with the interpretation criteria in the profer category. However, the results of the interviews showed that the implementation of the policy still experienced several obstacles. There are many inhibiting factors of implementation, namely inadequate budget, inadequate number of employees, incompatible mechanism of implementation of the protection of Indonesian Workers, the absence of vocational training center, and some of the prospective workers falsified identities. Local Government has made efforts to overcome the problem. It had to provide information about the protection of Indonesian workers (TKI) through print media and online media, giving direction to sub-districts to conduct entrepreneurship training activities for post-TKI and proposing additional staff to the regional employment agency.